SnO2 nano material with tin vacancy as well as preparation method and application of SnO2 nano material
By preparing SnO2 nanomaterials with tin vacancy, the problem of low detection sensitivity of existing materials is solved, and efficient detection of formaldehyde gas is achieved, with excellent sensing performance and long-term stability.
Patent Information
- Application Number
- CN202411946350.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-21
AI Technical Summary
The existing vacancy defective materials have low detection sensitivity in formaldehyde gas detection, making it difficult to meet the needs of efficient detection.
By preparing SnO2 nanomaterials with tin vacancy, the morphology and defect structure of the material are controlled by additives such as urea and sodium citrate, and a high-active site is formed to improve the adsorption and sensing performance of formaldehyde gas.
It realizes high sensitivity detection of formaldehyde gas molecules, improves the selectivity and long-term stability of the sensor, and has no potential risks to human health and the natural environment.
Smart Images

Figure CN119660786A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of SnO2 nanomaterials, and in particular relates to a SnO2 nanomaterial with tin vacancies and a preparation method and application thereof. Background Art
[0002] With the development of society, environmental safety issues have received increasing public attention. Formaldehyde, as a volatile, flammable, corrosive and toxic organic compound, is significantly irritating and corrosive to the human body, and poses a potential pollution to the environment. The main formaldehyde detection methods include infrared spectroscopy, labeling reagent method, gas chromatography-fluorescence detection and inductively coupled plasma mass spectrometry. The equipment used in these detection methods is expensive, the operation is complicated, and they are not suitable for rapid on-site detection. Therefore, the development of a gas sensor with efficient detection of formaldehyde gas is crucial for environmental monitoring.
[0003] Metal oxide semiconductors (MOS) have attracted wide attention in the fields of gas sensing, lithium batteries, photocatalysis, etc. due to their selectivity, theoretical performance, and charge transfer. In the field of gas sensing, tin oxide (SnO2) is a typical n-type semiconductor material with a wide band gap, which can improve the sensitivity and selectivity of detection through particle size adjustment, metal modification, and the formation of heterostructures. According to the MOS gas sensing principle, for example, SnO2, the surface ions adsorb oxygen, including superoxide ions (O 2 − ) and charged atoms (O − and O 2− ), plays a vital role in the reaction with the target gas. In view of the current problems, the development of new sensitive materials is of great significance for the development of gas sensors. Vacancy-type defects are a common and inherent defect in metal oxides, which have been proven to be an ideal material modification strategy. Because vacancies can not only produce unsaturated coordination sites to change the bonding strength, enabling them to interact with characteristic functional groups in specific VOC molecules, but also affect the electronic structure and charge distribution of the material, thereby causing changes in the material resistance, becoming an effective technical means to improve gas sensing performance. However, most of the current vacancy-type defect materials have the problem of low detection sensitivity. Summary of the invention
[0004] In view of the above-mentioned deficiencies in the prior art, the present invention provides a SnO2 nanomaterial with tin vacancies and a preparation method and application thereof. The SnO2 nanomaterial has high sensitivity to formaldehyde, so that the sensor has excellent sensing performance to formaldehyde gas molecules, which can effectively solve the problem of poor detection sensitivity of existing materials.
[0005] To achieve the above purpose, the technical solution adopted by the present invention to solve the technical problem is:
[0006] A method for preparing a SnO2 nanomaterial having tin vacancies comprises the following steps:
[0007] (1) At 0°C, a SnCl4·5H2O solution was prepared, and then urea and sodium citrate were added thereto in sequence to obtain a mixed solution. The mixed solution was reacted at 190-210°C for 15-25h, cooled naturally, and the precipitate was collected and dried to obtain a precursor 1;
[0008] (2) preparing a SnCl4·5H2O solution at 0°C, then adding urea thereto to obtain a mixed solution, reacting the mixed solution at 75-85°C for 11-13h, cooling naturally, collecting the precipitate, and drying to obtain a precursor 2;
[0009] (3) In an Ar atmosphere, precursor 1 and precursor 2 are placed separately in the same container, and then the temperature is raised to 450-550°C at a rate of 4-6°C / min and calcined for 4-6 hours. Precursor 1 material is collected, which is the SnO2 nanomaterial with tin vacancies.
[0010] Furthermore, the concentration of the SnCl4·5H2O solution in step (1) is 0.2-0.3 mmol / mL.
[0011] Furthermore, in step (1), the molar ratio of SnCl4·5H2O, urea and sodium citrate is 8-12:75-85:8-12.
[0012] Furthermore, the concentration of the SnCl4·5H2O solution in step (2) is 0.15-0.2 mmol / mL.
[0013] Furthermore, in step (2), the molar ratio of SnCl4·5H2O to urea is 2.5-3.5:1.
[0014] Furthermore, in steps (1) and (2), the drying temperature is 55-65° C. and the drying time is 10-14 h.
[0015] Furthermore, in step (3), the molar ratio of SnCl4·5H2O in precursor 1 and precursor 2 is 4:2.5-3.5.
[0016] A SnO2 nano material with tin vacancies is prepared by adopting the method.
[0017] The above-mentioned SnO2 nanomaterial with tin vacancies is used in the preparation of formaldehyde detectors.
[0018] The beneficial effects produced by the present invention are:
[0019] 1. The SnO2 nanomaterial with tin vacancies prepared by the present invention has highly active sites, which are conducive to promoting the adsorption of formaldehyde gas molecules, thereby promoting the mass transfer process in the gas sensing reaction and improving the sensing performance of formaldehyde gas molecules; and the material has high selectivity and long-term stability, and has no potential risks to human health and the natural environment.
[0020] 2. In the present invention, urea is added to the SnCl4·5H2O solution, and the urea and Sn 4+ The ions form a stable complex to control the morphology of the SnO2 nanomaterial; the addition of sodium citrate, which acts as both a complexing agent and a dispersant, helps to improve the dispersibility of the product and make the prepared SnO2 nanoparticles have good dispersibility.
[0021] 3. In the present invention, the precursor 1 and the precursor 2 are sintered together, the main purpose of which is to promote the formation of tin vacancy defects. Specifically, in the process of synthesizing nano SnO2 with metal tin defects in an inert atmosphere (Ar), the interstitial metal Sn in the precursor 1 is ionized to generate holes, and the holes compensate the charge through the holes. The formed holes can be captured by the metal cations in the precursor 2, and then tin vacancy defects are formed in the precursor 1, thereby improving the sensitivity of the material to formaldehyde detection. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 is the X-ray diffraction pattern of SnO2 nanomaterials with tin vacancies;
[0023] Figure 2 This is the X-ray spectrum of SnO2 nanomaterials with tin vacancies;
[0024] Figure 3 Schematic diagram of SnO2 nanomaterials with tin vacancies modified with gold intercalation electrodes;
[0025] Figure 4 The statistical graphs of the responses of SnO2 nanomaterials with tin vacancies to 100 ppm formaldehyde, ethanol, methanol, acetaldehyde, acetone, toluene and triethylamine gas molecules at different working temperatures;
[0026] Figure 5 The statistical diagram of the cyclic stability of SnO2 nanomaterials with tin vacancies;
[0027] Figure 6 This is a linear relationship diagram between the formaldehyde response value and concentration of SnO2 nanomaterials with tin vacancies. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention, that is, the embodiments described are only part of the embodiments of the present invention, rather than all of the embodiments.
[0029] Therefore, the following detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work are within the scope of protection of the present invention.
[0030] It should be noted that relational terms such as "first" and "second" are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprises a ..." does not exclude the existence of other identical elements in the process, method, article or device including the element.
[0031] The features and performance of the present invention are further described in detail below in conjunction with the embodiments and drawings.
[0032] Example 1
[0033] A SnO2 nanomaterial with tin vacancies, the preparation method of which comprises the following steps:
[0034] (1) At 0°C, 10 mmol SnCl4·5H2O was weighed and dissolved in 40 mL deionized water. The mixture was stirred magnetically for 10 min to form a uniform transparent solution to prepare a SnCl4·5H2O solution. Then, 80 mmol urea was added thereto and stirred for 10 min. Then, 10 mmol sodium citrate was added and stirred for 15 min to prepare a mixed solution. The mixed solution was subjected to hydrothermal reaction at 200°C for 20 h. The mixture was cooled naturally and the precipitate was collected and washed with deionized water and anhydrous ethanol for 6 times. The precipitate was dried in a vacuum oven at 60°C for 12 h to prepare a precursor 1.
[0035] (2) At 0°C, 7.5 mmol SnCl4·5H2O was dissolved in 40 mL ice deionized water, 2.5 mmol urea was added, and the mixture was stirred for 15 min to form a uniform mixed solution. The mixed solution was reacted at 80°C for 12 h, cooled naturally, and the precipitate was collected and washed with deionized water and anhydrous ethanol for 6 times, and dried in a vacuum oven at 60°C for 12 h to obtain precursor 2;
[0036] (3) In an Ar atmosphere, precursor 1 and precursor 2 are placed separately in the same tube furnace, heated to 500°C at a rate of 5°C / min and calcined for 5 h. Precursor 1 material is collected, which is the SnO2 nanomaterial with tin vacancies.
[0037] Example 2
[0038] A SnO2 nanomaterial with tin vacancies, the preparation method of which comprises the following steps:
[0039] (1) At 0°C, 10 mmol SnCl4·5H2O was weighed and dissolved in 50 mL deionized water. The solution was stirred magnetically for 10 min to form a uniform transparent solution to prepare a SnCl4·5H2O solution. Then, 75 mmol urea was added thereto and stirred for 10 min. Then, 8 mmol sodium citrate was added and stirred for 15 min to prepare a mixed solution. The mixed solution was subjected to hydrothermal reaction at 190°C for 25 h. The solution was cooled naturally and the precipitate was collected and washed with deionized water and anhydrous ethanol for 6 times. The precipitate was dried in a vacuum oven at 55°C for 14 h to prepare a precursor 1.
[0040] (2) At 0°C, 7.5 mmol SnCl4·5H2O was dissolved in 50 mL ice deionized water, 3 mmol urea was added, and the mixture was stirred for 15 min to form a uniform mixed solution. The mixed solution was reacted at 75°C for 13 h, cooled naturally, and the precipitate was collected and washed with deionized water and anhydrous ethanol for 6 times, and dried in a vacuum oven at 55°C for 14 h to obtain precursor 2;
[0041] (3) In an Ar atmosphere, precursor 1 and precursor 2 were placed separately in the same tube furnace, heated to 550°C at a rate of 4°C / min, and calcined for 6 h. Precursor 1 material was collected, which was the SnO2 nanomaterial with tin vacancies.
[0042] Example 3
[0043] A SnO2 nanomaterial with tin vacancies, the preparation method of which comprises the following steps:
[0044] (1) At 0°C, 10 mmol SnCl4·5H2O was weighed and dissolved in 33 mL deionized water. The mixture was stirred magnetically for 10 min to form a uniform transparent solution to prepare a SnCl4·5H2O solution. Then, 85 mmol urea was added thereto and stirred for 10 min. Then, 12 mmol sodium citrate was added and stirred for 15 min to prepare a mixed solution. The mixed solution was subjected to hydrothermal reaction at 210°C for 15 h. The mixture was cooled naturally and the precipitate was collected and washed with deionized water and anhydrous ethanol for 6 times. The precipitate was dried in a vacuum oven at 60°C for 12 h to prepare a precursor 1.
[0045] (2) At 0°C, 7.5 mmol SnCl4·5H2O was dissolved in 37.5 mL ice deionized water, and 2.14 mmol urea was added. The mixture was stirred for 15 min to form a uniform mixed solution. The mixed solution was reacted at 85°C for 11 h, cooled naturally, and the precipitate was collected and washed with deionized water and anhydrous ethanol for 6 times. It was dried in a vacuum oven at 55°C for 14 h to obtain precursor 2.
[0046] (3) In an Ar atmosphere, precursor 1 and precursor 2 were placed separately in the same tube furnace, heated to 550°C at a rate of 6°C / min and calcined for 4 h. Precursor 1 material was collected, which was the SnO2 nanomaterial with tin vacancies.
[0047] Comparative Example 1
[0048] A SnO2 nanomaterial, the preparation method of which comprises the following steps:
[0049] (1) At 0°C, 10 mmol SnCl4·5H2O was weighed and dissolved in 40 mL deionized water. The mixture was stirred magnetically for 10 min to form a uniform transparent solution to prepare a SnCl4·5H2O solution. Then, 80 mmol urea was added thereto and stirred for 10 min. Then, 10 mmol sodium citrate was added and stirred for 15 min to prepare a mixed solution. The mixed solution was subjected to hydrothermal reaction at 200°C for 20 h. The mixture was cooled naturally and the precipitate was collected and washed with deionized water and anhydrous ethanol for 6 times. The precipitate was dried in a vacuum oven at 60°C for 12 h to prepare a precursor.
[0050] (2) In an Ar atmosphere, the precursor was placed in a tube furnace, heated to 500°C at a rate of 5°C / min and calcined for 5 h. The precursor 1 material was collected, which was the SnO2 nanomaterial with tin vacancies.
[0051] Comparative Example 2
[0052] A SnO2 nanomaterial, the preparation method of which comprises the following steps:
[0053] (1) At 0°C, 10 mmol SnCl4·5H2O was weighed and dissolved in 40 mL deionized water. The mixture was stirred magnetically for 10 min to form a uniform transparent solution to prepare SnCl4·5H2O solution. The solution was subjected to hydrothermal reaction at 200°C for 20 h. The solution was cooled naturally and the precipitate was collected. The precipitate was washed with deionized water and anhydrous ethanol for 6 times and dried in a vacuum oven at 60°C for 12 h to obtain precursor 1.
[0054] (2) At 0°C, 7.5 mmol SnCl4·5H2O was dissolved in 40 mL ice deionized water. The solution was reacted at 80°C for 12 h, cooled naturally, and the precipitate was collected and washed with deionized water and anhydrous ethanol for 6 times. It was dried in a vacuum oven at 60°C for 12 h to obtain precursor 2.
[0055] (3) In an Ar atmosphere, precursor 1 and precursor 2 are placed together in a tube furnace, the temperature is raised to 500°C at a rate of 5°C / min, and calcined for 5 h. Precursor 1 material is collected, which is the SnO2 nanomaterial with tin vacancies.
[0056] Test example
[0057] The changes in the crystal structure and composition of the SnO2 nanomaterial with tin vacancies in Example 1 were analyzed by X-ray diffraction. Figure 1 It can be seen that the characteristic diffraction peaks of each sample can be attributed to square rutile SnO2 (JCPDS No. 77-0448), indicating that SnO2 nanomaterials have been successfully prepared.
[0058] The surface chemical state of SnO2 nanomaterials with tin vacancies was analyzed by X-ray spectroscopy. Figure 2 It can be seen that the Sn 3d 3 / 2 and Sn 3d 5 / 2 The two peaks are located at 496.1 and 486.5 eV, respectively.
[0059] Sensor preparation: 0.03 g of SnO2 with tin vacancies synthesized in Example 1 was weighed and mixed with 0.57 g of glycerol, 0.3 g of ethylene glycol and 100 μL of H2O using an analytical balance to form a uniform slurry. 20 μL of the prepared slurry was coated on the surface of an 8 mm × 10 mm × 0.6 mm alumina ceramic substrate, and the coated electrode sheet was placed in a 120°C oven for 2 h and sintered at 400°C in a N2 atmosphere for 2 h to obtain a SnO2 nanomaterial gas sensor with tin vacancies. The prepared gas sensor was then placed on a heating table and aged at 200°C in an air environment for 48 h.
[0060] Gas sensing measurements of the sensor were carried out at a relative humidity of 28%. The working temperatures selected were room temperature, 50, 100, 150, 200, 250 and 300 °C. The sensing responses of the SnO2 sensor to 100 ppm formaldehyde at different working temperatures are shown in Figure 2. Figure 4 shown.
[0061] The optimal operating temperature of the SnO2 sensor is 150℃, and the sensitivity to formaldehyde is as high as 158.6. The six gases, ethanol, methanol, acetaldehyde, acetone, toluene and triethylamine, were tested under 100ppm. The results showed that the response values of other gases were much smaller than the response value to formaldehyde, proving that the SnO2 sensor has excellent selectivity for formaldehyde.
[0062] The SnO2 nanomaterials in Comparative Example 1 and Comparative Example 2 were weighed respectively, and SnO2 sensors were prepared according to the above method and tested under the same conditions.
[0063] The results show that the sensitivity of the sensors in Comparative Examples 1 and 2 to formaldehyde is only 5.3 and 10.6 respectively. The sensitivity of the sensor in Example 1 is increased by up to 30 times at the optimal working temperature compared with the sensors in Comparative Examples 1 and 2.
[0064] The sensor was tested for 12 cycles in a 100 ppm formaldehyde atmosphere at 150°C and 32-35% relative humidity ( Figure 5 ), the SnO2 sensor with tin vacancies exhibits excellent response and recovery trend, with no obvious attenuation compared to the initial response.
[0065] The linear relationship between the response of the SnO2 sensor with tin vacancies and the formaldehyde concentration (0.1-100 ppm) was investigated at 150 °C and 32-35% relative humidity, as shown in Figure 2. Figure 6 The results show that the fitting slope of the sensor is 2.0877, and there is a good linear relationship between the formaldehyde response value and the concentration (0.1100 ppm), and the fitting degree (R 2 ) was 0.86, further demonstrating its superior detection ability for formaldehyde.
Claims
1. A method for preparing a SnO2 nanomaterial having tin vacancies, characterized in that: The following steps are involved: (1) At 0°C, a SnCl4·5H2O solution was prepared, and then urea and sodium citrate were added thereto in sequence to obtain a mixed solution. The mixed solution was reacted at 190-210°C for 15-25h, cooled naturally, and the precipitate was collected and dried to obtain a precursor 1; (2) preparing a SnCl4·5H2O solution at 0°C, then adding urea thereto to obtain a mixed solution, reacting the mixed solution at 75-85°C for 11-13h, cooling naturally, collecting the precipitate, and drying to obtain a precursor 2; (3) In an Ar atmosphere, precursor 1 and precursor 2 are placed separately in the same container, and then the temperature is raised to 450-550°C at a rate of 4-6°C / min and calcined for 4-6 hours. Precursor 1 material is collected, which is the SnO2 nanomaterial with tin vacancies.
2. The method for preparing SnO2 nanomaterials having tin vacancies according to claim 1, characterized in that: Step (1) The concentration of SnCl4·5H2O solution is 0.2-0.3 mmol / mL.
3. The method for preparing SnO2 nanomaterials having tin vacancies according to claim 1, characterized in that: Step (1) The molar ratio of SnCl4·5H2O, urea and sodium citrate is 8-12:75-85:8-12.
4. The method for preparing SnO2 nanomaterials having tin vacancies according to claim 1, characterized in that: The concentration of the SnCl4·5H2O solution in step (2) is 0.15-0.2 mmol / mL.
5. The method for preparing SnO2 nanomaterials having tin vacancies according to claim 1, characterized in that: In step (2), the molar ratio of SnCl4·5H2O to urea is 2.5-3.5:
1.
6. The method for preparing SnO2 nanomaterials having tin vacancies according to claim 1, characterized in that: In steps (1) and (2), the drying temperature is 55-65°C and the drying time is 10-14h.
7. The method for preparing SnO2 nanomaterials having tin vacancies according to claim 1, characterized in that: In step (3), the molar ratio of SnCl4·5H2O in precursor 1 and precursor 2 is 4:2.5-3.
5.
8. A SnO2 nanomaterial with tin vacancies, characterized in that: The method according to any one of claims 1 to 7 is adopted.
9. Use of the SnO2 nanomaterial with tin vacancies as claimed in claim 8 in the preparation of a formaldehyde detector.